The Growth and Development of Non Carcass Organ's of Bali Cattle - Harapin Hafid; Juliadin (Talenta Publisher, 2020)
This study aims to determine the pattern of growth and development of non carcass organs in Bali cattle males and females. And this research is expected to provide information to the public and farmers about biological phenomena organ growth and development of non carcass Bali cattle males and females, as well as basic data in making estimates, the production of non carcass organs as well as information for research selanjutnuya. Samples of this research data is withheld Bali cattle (slaughter) in Slaughterhouse Kendari. Observations were carried out on cattle by 28 head with 2-3 years of age and body weight between 90-300 kg. The method used in this research is Huxley allometric equation Y = axb transformed into logarithms log equation is Y = log a + b log x and the real difference test with a test -student, the observed variables is slaughter weight, non carcass weight and the weight of the non carcass parts of Bali cattle male and female as the head, front legs, hind legs, skin, lungs, liver, intestines and stomach. The results showed that the coefficient of growth of non carcass organs (offal) Bali cattle male and female is as follows (b = 0.25 and 0.40). The coefficient of non carcass organ growth clearly different one (p<0.05), which means non carcass weights have time to cook early development when compared to the overall body growth. While the pattern of growth and development of non-organ parts of Bali cattle carcass relative male and female alike, with the growth coefficient b<1. The conclusion of this study is the growth of non carcass organs and parts non organ Bali cattle carcass of males and females have a pattern of rapid growth/early ripe with weight. It is advisable to do further research with a sample of cattle that more and consider cutting in series (serial slaughter) at certain ages